Experimental Studies on Abrasive Water Jet Cutting of Nano SiC Particles Filled Hybrid Basalt-Glass Fibre-Reinforced Epoxy Composites - Vijayabhaskar, S.; Rajmohan, T.; Vijayan, D.; Palanikumar, K. (Journal of Research Updates in Polymer Science, 2023)
Abrasive water jet machining (AWJM) is extensively beneficial in machining materials that are hard to cut. This investigation deals with AWJM of Nano SiC filled Epoxy reinforced with basalt-glass fiber hybrid composite. The composite is prepared by compression moulding technique. Experimental trails are performed to evaluate the impact of every process parameter on the responses i.e., surface roughness (Ra) and Material Removal Rate (MRR). The experiments are conducted by changing the standoff distance (SD), traverse speed (TS) and water pressure. The performance of the conducted experiment is analysed using a Swarm intelligence algorithm. Surface roughness and MRR are maximized by using the combination of optimum process parameter levels of 9.72 mm/min speed, 5.78 mm stand-off distance and 553 MPa jet pressure. Scanning Electron Microscopic (SEM) images are employed in detecting the morphology of machined surface and confirmed the presence of voids and fibre pull-out.